Building Affective Community and Navigating Censorship: Fengli In Action’s Feminist Space on WeChat - Xue, Fengjiao (My University, 2025)
Abstract: This thesis examines the construction of an affective feminist community and the navigation of digital censorship through the case study of Fengli In Action, an online feminist community which was active on WeChat during China’s COVID-19 lockdown period, and its programme Fireside Talks. The purpose of the research is to explore how grassroots feminist communities build emotional solidarity, address internal and external challenges, and negotiate political restrictions in a censored digital environment. The study employs qualitative research methods, combining ethnography, netnography, and interviews with eight former participants and organisers of Fengli’s Fireside Talks programme. The research data consist of WeChat Official Account materials and in-depth interviews. The findings reveal that while Fengli created a temporary safe space fostering emotional support and feminist dialogue, it also faced limitations including exclusionary practices, ideological tensions, generational divides, and challenges in sustaining long-term engagement. The study concludes that affective connections provided crucial emotional refuge under authoritarian conditions but were fragile, short-lived, and insufficient to overcome structural constraints, reflecting broader tensions within contemporary Chinese feminist activism.
Keywords: Digital Feminism, Affective Community, WeChat, Censorship, Feminist Activism in China